On the Relationship between Language and Culture - Harutyunyan, Kristine (Armenian Folia Anglistika, 2011)
The issue of the interrelation between language and culture has always been in the center of attention of various representatives of different sciences. When the language is used in the context of communication, it gets connected with the culture by numerous bonds. The members of the society not only express their experience through the language. Rather they create it. Thus, the language expresses and embodies the cultural reality. The language of each society is, in fact, a part of its culture and reflects the important cultural features of the objects, institutions and actions of the given society. In order to understand the meaning of words, it is necessary to have social and individual perception. Thus, while investigating the interrelation between language and culture, it is necessary to take into account both psycholinguistic and ethnolinguistic approaches.